PENGARUH KONSENTRASI DAN VARIETAS TEPUNG UBI JALAR TERHADAP AKTIVITAS ANTIOKSIDAN DAN KARAKTERISTIK SENSORI CILOK AYAM - Olindiana Desari; Sri Handayani; Rosyida Fajri Rinanti (BUANA SAINS, 2025)
Cilok is a traditional snack food made from tapioca flour with limited nutritional value. Diversification with chicken meat and sweet potato flour has the potential to enhance the nutritional and functional value of the product, particularly as a source of natural antioxidants. This study aimed to analyze the effect of variety (yellow, purple, and white) and concentration (10% and 20%) of sweet potato flour on the antioxidant activity and sensory characteristics (color, aroma, taste, and texture) of chicken cilok, and to determine the optimal formulation. The experimental design used a Randomized Block Design (RBD) with 7 treatments and 3 replications. Antioxidant activity was analyzed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, while sensory evaluation was conducted using a hedonic scaling method (scale 1–7) involving 20 semi-trained panelists. Data were analyzed by ANOVA and further tested with LSD at ?=0.05, while sensory data were analyzed using the Friedman test. The result showed that concentration and variety of sweet potato flour had a significant effect (p0.05) on antioxidant activity and a highly significant effect (p0.01) on all sensory attributes. The highest antioxidant activity was obtained in treatment P5 (80% chicken meat + 20% purple sweet potato flour) at 7.040 ± 0.30% (DPPH radical scavenging activity). The same treatment also received the highest overall sensory scores (color: 6.53; aroma: 5.57; taste: 5.82; texture: 5.40) and was selected as the best formulation based on the effectiveness index analysis. The addition of 20% purple sweet potato flour can increase antioxidant activity and is sensorily acceptable, thus having potential to be developed as a functional chicken cilok.